Success factors to facilitate continuous improvement culture within Saudi non-profit organizations - Almaiman, Sulaiman; McLaughlin, Patrick (Cranfield University, 2016)
This paper explores the organizational and cultural factors facilitate a continuous improvement in Saudi non-profit organizations. Several researchers have shown that organizational culture has a significant impact on an organization. The literature shows that the nonprofit sector is often neglected. There is a similar lack of empirical research on this topic explicit to Saudi Arabia Grounded theory was used to explore factors from the literature and empirical data. Nine factors were extracted from the literature. Nineteen factors emerged from seventeen interviews conducted in the non-profit sector in Saudi Arabia.